Digital Innovation Design of Tourism Destination Marketing Website Using Design Thinking Method (JESII: Journal of Elektronik Sistem InformasI, 2023)
This study aims to design a marketing website for special interest tourism destinations in North Banjar Resident. The method used is design thinking. The design thinking method has five stages: empathize, define, ideate, prototype, and test. At the empathize stage, the needs of system users are classified based on the characteristics of the user as a host or guest. In the define stage, the problem statement technique is used to define the problems and needs of users into four parts: lack of awareness and exposure, limited digital infrastructure, the limited availability of tourism-related infrastructure, and the lack of tourism-related data. At the ideation stage, the main problem identified related to the marketing of special interest tourist destinations is the lack of tourism-related data, so the idea to solve the problem is through the design of a website that accommodates all information about destinations and events, hotel accommodation services, resorts and cottages, vehicle rental services, and travel experiences to North Banjar which are shared in the form of articles to short videos. At the prototype stage, the database and interface design are designed according to the analysis results at the empathize, define, and ideate stages. Furthermore, at the testing stage, aspirations about prototypes are carried out through posters and short videos to gain insight into the subsequent development. Thus, marketing special interest tourist destinations becomes more effective and efficient using a website-based digital platform.